Implementasi Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Geografi pada Materi Litosfer Siswa Kelas X SMA Negeri 1 Pinogaluman - Salsabila Rahmatia Baladraf; M. Iqbal Liayong Pratama; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
This study aims to describe the implementation of differentiated instruction and examine the improvement in Geography learning outcomes among Grade X-1 students on the lithosphere topic at SMA Negeri 1 Pinogaluman. The study employed classroom action research based on the Kemmis and McTaggart model and was conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 30 students. Before the intervention, a learning-style assessment was administered to identify students’ learning characteristics. Data were collected through learning achievement tests, observations, and documentation. Differentiated instruction was implemented by adjusting learning materials, student worksheets, learning stimuli, and activities while considering students’ characteristics. Improvements in the second cycle included the use of posters as visual stimuli, barcodes to access videos and supporting information, and more intensive teacher guidance during group activities. The results showed that the students’ mean score increased from 66 in the first cycle to 81.33 in the second cycle. Classical mastery also increased from 43.33% to 86.67%, while the number of students who achieved mastery increased from 13 to 26. The achievement in the second cycle met the predetermined success criterion. These findings indicate that differentiated instruction can improve students’ Geography learning outcomes on the lithosphere topic.